Crystal of 4, 4 '-bis (1, 1-bis (4-hydroxy-3-methylphenyl) ethyl) biphenyl and method for producing same
By crystallization using alkyl acetates and cyclic saturated hydrocarbon solvents in aqueous sodium hydroxide and aqueous phosphoric acid, 4,4'-bis(1,1-bis(4-hydroxy-3-methyl was successfully prepared by crystallization in aqueous sodium hydroxide and aqueous phosphoric acid solution. The crystallization of ylphenyl)ethyl)biphenyl solves the crystallization problem of failure to effectively produce the compound in the prior art, and achieves high purity and high efficiency industrial production.
Patent Information
- Application Number
- CN202380038745.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-25
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art has not been able to effectively produce and obtain 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl crystals, and their physical properties and manufacturing methods are not detailed. Report.
After neutralization in aqueous sodium hydroxide and aqueous phosphoric acid solution, crystallization using alkyl acetates and cyclic saturated hydrocarbon solvents was obtained to obtain Compound A crystal with specific endothermic peak temperatures and X-ray diffraction peaks. .
It has achieved high-purity crystallization of Compound A, which is suitable for industrial production, improves the bulk density and reaction efficiency of Compound A, and solves the problems of conveying, preserving and reaction efficiency in industrial production.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl and a method for producing the same. Background Art
[0002] Tetraphenol compounds can be used as raw materials for epoxy resins used in packaging materials, laminated materials, electrical insulating materials, etc. for integrated circuits, curing agents for epoxy resins, color developers or anti-fading agents for thermal recording, raw materials for electronic materials or photosensitive materials, etc. In addition, they are also widely used as additives such as antioxidants, bactericides, antibacterial and antifungal agents, and inclusion compounds.
[0003] As a method for producing a tetraphenol compound, for example, Patent Document 1 describes in detail a method of reacting phenols with 4,4′-diacylbiphenyls in the presence of hydrogen chloride gas using 3-mercaptopropionic acid as a promoter to perform dehydration condensation.
[0004] On the other hand, 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl (hereinafter sometimes referred to as "Compound A"), which is one type of tetraphenol compound, is described in Patent Document 2 only by its chemical name as a specific example of the compound, and no specific production method or physical properties of Compound A have been reported.
[0005] Furthermore, of course, crystals of Compound A could not be obtained.
[0006] Patent Literature Patent Document 1: Japanese Patent Application Laid-Open No. 08-027052 Patent Document 2: Japanese Patent Application Publication No. 2001-235872 Summary of the invention The present invention has been accomplished against the background of the above circumstances, and an object of the present invention is to provide an isolated product of compound A in a form suitable for industrial production.
[0007] The present inventors conducted intensive studies on a method for isolating compound A and, as a result, discovered for the first time that compound A can be isolated as a crystal, thereby completing the present invention.
[0008] The present invention is as follows.
[0009] 1. A crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl.
[0010] 2. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to 1., characterized in that the endothermic peak top temperature obtained by differential scanning calorimetry analysis is in the range of 150 to 165°C.
[0011] 3. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to 1., characterized in that it has diffraction peaks at diffraction angles 2θ of 7.8±0.2°, 13.8±0.2° and 16.9±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα rays.
[0012] 4. A method for producing a crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to 1. or 2., characterized in that it comprises a step of crystallizing 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl from a solution containing an alkyl acetate solvent having a total carbon number of 4 to 8 and a cyclic saturated hydrocarbon solvent having a carbon number of 5 to 8.
[0013] 5. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to 1., characterized in that the endothermic peak top temperature obtained by differential scanning calorimetry analysis is in the range of 120-130°C, 170-185°C and 235-245°C.
[0014] 6. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to 1., characterized in that it has diffraction peaks at diffraction angles 2θ of 11.1±0.2° and 13.4±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0015] 7. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to 1., characterized in that it has diffraction peaks at diffraction angles 2θ of 10.8±0.2° and 16.9±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0016] 8. A method for producing a crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl as described in 1. or 5., characterized in that it includes a step of crystallizing 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl from a solution containing an alkyl acetate solvent having a total carbon number of 4 to 8 and an aromatic hydrocarbon solvent having a carbon number of 7 to 10.
[0017] The crystals of compound A of the present invention have good operability and are therefore suitable for industrial production, and can efficiently obtain high-purity compound A. In addition, due to the high bulk density, a large amount of compound A can be filled in a container of a certain volume, thereby achieving excellent transportation efficiency, storage efficiency, reaction efficiency, etc.
[0018] The method for producing crystals of Compound A of the present invention can isolate Compound A into crystals having good handleability and high bulk density, and can produce Compound A with high purity as an industrially feasible and efficient production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of Crystal α of Compound A obtained in Example 1.
[0020] Figure 2 This is a diagram showing a graph of powder X-ray diffraction (PXRD) measurement of Crystal α of Compound A obtained in Example 1.
[0021] Figure 3 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of Crystal α of Compound A obtained in Example 2.
[0022] Figure 4 This is a diagram showing a graph of powder X-ray diffraction (PXRD) measurement of Crystal α of Compound A obtained in Example 2.
[0023] Figure 5 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of crystal β of compound A obtained in Example 3.
[0024] Figure 6 This is a diagram showing a chart of powder X-ray diffraction (PXRD) measurement of crystal β of compound A obtained in Example 3.
[0025] Figure 7 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of crystal β of compound A obtained in Example 4.
[0026] Figure 8 This is a diagram showing a chart of powder X-ray diffraction (PXRD) measurement of crystal β of compound A obtained in Example 4.
[0027] Fig. 9 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of crystal β of compound A obtained in Example 5.
[0028] Fig.10 This is a diagram showing a chart of powder X-ray diffraction (PXRD) measurement of crystal β of compound A obtained in Example 5.
[0029] Fig.11 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of crystal β of compound A obtained in Example 6.
[0030] Fig.12 This is a diagram showing a chart of powder X-ray diffraction (PXRD) measurement of crystal β of compound A obtained in Example 6.
[0031] Fig.13 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of crystal β of compound A obtained in Example 7.
[0032] Fig.14 This is a diagram showing a chart of powder X-ray diffraction (PXRD) measurement of crystal β of compound A obtained in Example 7.
[0033] Fig.15 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of the crystals of Compound A obtained in Reference Example 1.
[0034] Fig.16 This is a diagram showing a graph of powder X-ray diffraction (PXRD) measurement of the crystal of Compound A obtained in Reference Example 1.
[0035] Fig.17 This is a diagram showing a graph of differential scanning calorimetry (DSC) data of the crystals of Compound A obtained in Reference Example 2.
[0036] Fig.18 This is a diagram showing a chart of powder X-ray diffraction (PXRD) measurement of the crystals of Compound A obtained in Reference Example 2. DETAILED DESCRIPTION
[0037] The present invention is described in detail below.
[0038] The 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl (Compound A) according to the present invention is a compound having the following chemical structure.
[0039] [Chemistry 1]
[0040] The method for producing compound A is not particularly limited. For example, as shown in the following reaction formula, 1 equivalent of compound A and 2 equivalents of water are produced by dehydration condensation reaction of 4 equivalents of o-cresol and 1 equivalent of 4,4'-diacylbiphenyl.
[0041] [Chemistry 2]
[0042] In the method for producing the compound A of the above reaction formula, the reaction conditions are described below.
[0043] The amount of o-cresol used is preferably in the range of 4 to 20 moles relative to 1 mole of 4,4'-diacylbiphenyl, more preferably in the range of 5 to 15 moles, and particularly preferably in the range of 8 to 12 moles. If the amount of o-cresol used is less than 4 moles, the reaction will slow down, and in addition to the target compound A, byproducts such as polynuclear bodies obtained by further condensation of 4,4'-diacylbiphenyl or o-cresol will increase, so it is not preferred. In addition, if more than 20 moles are used, the reaction rate is improved, but the recovery amount of unreacted o-cresol increases, and productivity decreases, so it is not practical.
[0044] The reaction temperature is preferably in the range of 0 to 80°C, more preferably in the range of 30 to 60°C.
[0045] The reaction is usually carried out under normal pressure, but may be carried out under increased or reduced pressure depending on the boiling point of the organic solvent used so that the reaction temperature is within the above range.
[0046] During the reaction, the mixing method of the raw materials is not particularly limited. From the perspective of reaction selectivity, it is preferred to mix a mixed solution of 4,4'-diacetylbiphenyl and the remaining amount of o-cresol into a solution containing a portion of o-cresol, a catalyst, and a co-catalyst as required. In the case of such a mixing method, the mixing is carried out in a manner that the time required for mixing is in the range of 0.5 to 5 hours. The reaction is carried out in a manner that the mixed liquid becomes the amount of the raw materials used.
[0047] The reaction time varies depending on the amount of the catalyst and the reaction temperature, but is usually in the range of 1 to 20 hours, and is preferably completed in the range of 1 to 10 hours.
[0048] The end point of the reaction can be confirmed by liquid chromatography analysis or gas chromatography analysis. The point in time when unreacted 4,4'-diacylbiphenyl disappears or when the increase of the target compound A is no longer confirmed is preferably regarded as the end point of the reaction.
[0049] <Catalyst> As for the manufacturing method of compound A in the above reaction formula, any acid catalyst of inorganic acid and organic acid can be used as a catalyst. As inorganic acid, hydrogen chloride gas, hydrochloric acid, sulfuric acid, phosphoric acid, sulfuric anhydride, etc. can be listed, as organic acid, aromatic sulfonic acid such as benzenesulfonic acid and p-toluenesulfonic acid, alkanesulfonic acid with 1 to 4 carbon atoms such as methanesulfonic acid and ethanesulfonic acid, trifluoromethanesulfonic acid, trichloroacetic acid, etc. can be listed. In addition, metal halides such as aluminum chloride and ferric chloride or solid acids such as cation exchange resins can also be used as catalysts.
[0050] Among these, organic acids are preferably used. Among organic acids, alkanesulfonic acids having 1 to 4 carbon atoms are more preferred, methanesulfonic acid or ethanesulfonic acid is further preferred, and methanesulfonic acid is particularly preferred. The amount of the alkanesulfonic acid used is preferably in the range of 0.1 to 5.0 mol, more preferably in the range of 0.5 to 2.0 mol, relative to 1 mol of the 4,4'-diacylbiphenyls.
[0051] <Promoter> The manufacturing method of compound A in the above reaction formula can be combined with a catalyst as needed, and a thiol compound can be used as a co-catalyst. As a thiol compound, as long as it is a compound with a thiol group and does not have an adverse effect on the reaction selectivity, etc., there is no particular limitation. As such a compound, for example, carboxylic acids with a thiol group such as 3-mercaptopropionic acid and thioglycolic acid, alkyl thiols with carbon numbers of 1 to 12 such as methyl mercaptan, 1-octyl mercaptan (octyl mercaptan), 1-dodecyl mercaptan (lauryl mercaptan), and mercapto alcohols such as mercaptoethanol and mercaptobutanol can be listed. Among them, alkyl thiols with carbon numbers of 1 to 12 such as 1-octyl mercaptan are preferred. In addition, it can also be used in the state of an aqueous solution of a sodium salt.
[0052] When the thiol compound is used, the amount used is preferably in the range of 1 to 10% by weight relative to 4,4'-diacylbiphenyl. If it is less than 1% by weight, it cannot fully function as a co-catalyst, and even if it exceeds 10% by weight, it cannot further function as a co-catalyst and the selectivity is almost the same.
[0053] <Reaction solvent> In the manufacturing method of compound A in the above reaction formula, if there is no problem with operability, there is no need to use a reaction solvent. However, a reaction solvent can also be used to make the operability during industrial production better. The reaction solvent used is not particularly limited as long as it is a solvent that does not distill from the reaction vessel at the reaction temperature and is inactive for the reaction. For example, it can be listed: aromatic hydrocarbons such as toluene, xylene, and benzene; halogenated aromatic hydrocarbons such as chlorobenzene and dichlorobenzene; aliphatic hydrocarbons such as pentane, n-hexane, cyclohexane, and heptane; aliphatic alcohols such as methanol, n-butanol, tert-butanol, and cyclohexanol; aliphatic or cyclic ethers such as diethyl ether, diisopropyl ether, methyl tert-butyl ether, diphenyl ether, tetrahydrofuran, and dioxane. In the reaction solvent, aromatic hydrocarbons and halogenated aromatic hydrocarbons are preferred, and aromatic hydrocarbons are more preferred. The amount used is not particularly limited, but is generally in the range of 0.1 to 10 times by weight, more preferably 0.1 to 2 times by weight, and even more preferably 0.1 to 1 times by weight relative to o-cresol from the viewpoint of economic efficiency.
[0054] The manufacturing method of compound A in the above reaction formula is to generate water by the dehydration condensation reaction of o-cresol and 4,4'-diacylbiphenyl. By reacting under dehydration conditions that can remove the water in the reaction system such as the water generated by the reaction or the water contained in the catalyst used, the reaction can be carried out faster than in the case of no dehydration, the generation of by-products is suppressed, and the target can be obtained in a higher yield, so it is preferred. As a dehydration method, there is no particular limitation, for example, dehydration by adding a dehydrating agent, dehydration by decompression, dehydration by azeotropy with a solvent under normal pressure or reduced pressure, etc. The dehydrating agent that can be added as needed is not particularly limited, and examples thereof include: organic dehydrating agents having an orthoester skeleton, such as trimethyl orthoformate, triethyl orthoformate, trimethyl orthoacetate, triethyl orthopropionate, trimethyl orthobutyrate, trimethyl orthoisobutyrate, and 1,1,1-trimethoxyoctane; zeolites such as molecular sieve (3A) and molecular sieve (4A); inorganic anhydrous salts that may contain crystal water in their molecules, such as calcium chloride (anhydrous), calcium sulfate (anhydrous), magnesium chloride (anhydrous), magnesium sulfate (anhydrous), potassium carbonate (anhydrous), potassium sulfide (anhydrous), potassium sulfite (anhydrous), sodium sulfate (anhydrous), sodium sulfite (anhydrous), and copper sulfate (anhydrous).
[0055] <Post-reaction treatment> The post-treatment method of the production method of compound A in the above reaction formula is described below.
[0056] The obtained reaction mixture is preferably subjected to post-treatment before the crystallization method of the present invention described below is implemented. As post-treatment, for example, alkaline water such as sodium hydroxide aqueous solution is added to the reaction mixture to neutralize the acid catalyst used; after adding a solvent such as toluene or xylene that can dissolve compound A and can be separated from water as needed, the oil phase containing compound A is washed with water; and the solvent or o-cresol used in excess in the reaction is removed by distillation.
[0057] As the compound A to be subjected to the crystallization method of the present invention described later, for example, a distillation residue containing the compound A obtained by removing the solvent or o-cresol by distillation from the reaction mixture as described above; or the compound A subjected to column chromatography; crystals obtained by the crystallization method of the present invention; and crystals obtained by a crystallization method other than the crystallization method of the present invention can be used.
[0058] <Crystal of the present invention: Crystal α> One of the crystals of compound A in the present invention is a crystal having an endothermic peak top temperature in the range of 150 to 165°C obtained by differential scanning calorimetry, or having diffraction peaks at diffraction angles 2θ of 7.8±0.2°, 13.8±0.2° and 16.9±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, and having any one or both of the characteristics of "the above endothermic peak top temperature" and "the above powder X-ray diffraction peak spectrum" (hereinafter referred to as "crystal α").
[0059] The endothermic peak top temperature of the crystal α obtained by differential scanning calorimetry is preferably in the range of 152 to 165°C, more preferably in the range of 154 to 165°C, and particularly preferably in the range of 155 to 163°C.
[0060] The endothermic peak top temperature of Crystal α obtained by differential scanning calorimetry may have an endothermic peak top temperature in the range of 237 to 245° C. other than the above range. The endothermic peak top temperature is more preferably in the range of 238 to 245° C., particularly preferably in the range of 238 to 243° C.
[0061] In the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, the crystal α preferably has diffraction peaks at diffraction angles 2θ of 12.1±0.2° and 13.0±0.2° in addition to the above-mentioned diffraction peaks, and further, more preferably has diffraction peaks at 20.9±0.2° and 21.7±0.2°, and further, particularly preferably has diffraction peaks at 15.5±0.2° and 17.8±0.2°.
[0062] The purity of compound A in crystal α is preferably 97.0 area % or more, more preferably 97.5 area % or more, and further preferably 98.0 area % or more. The purity of compound A is calculated by the following formula using the total peak area observed when analyzing by ultra-high performance liquid chromatography, the peak area of compound A, and the peak area of various solvents by preparing a sample of a methanol solution of crystal α at a concentration in the range of 25 to 35 mg / 50 mL.
[0063] The above-mentioned ultra-high performance liquid chromatography analysis is performed using the following analysis equipment and analysis conditions, or analysis equipment and analysis conditions equivalent thereto.
[0064] [Calculation formula] "Purity of Compound A" = ("Peak area of Compound A" ÷ "Total peak area") × {100% ÷ (100% - "Area % of various solvents")} <Equipment and Conditions> Device: Shimadzu UFLC LC-20 series / manufactured by Shimadzu Corporation Pump: LC-20AD Column oven: CTO-20A Detector: SPD-20A Chromatographic column: HALOC18 3.0×75mm / manufactured by Shimadzu GLC Corporation Incubator temperature: 50℃ Flow rate: 0.7mL / min Mobile phase: (A) 0.2 vol% acetic acid aqueous solution, (B) methanol Gradient conditions: (B) Volume % (time elapsed from the start of analysis) 50% (0 minutes) → (10 minutes) → 100% (15 minutes) Sample injection volume: 1~5μL Detection wavelength: 280nm The loose bulk density of crystalline α is preferably 0.25 to 0.40 g / cm 3 More preferably, it is 0.28 to 0.40 g / cm 3 The range is more preferably 0.30 to 0.40 g / cm 3 The value of the loose bulk density is a value calculated by dividing the weight value of the weighed crystal by the volume value measured immediately after the weighed crystal is filled in a measuring cylinder.
[0065] The tapped bulk density of crystalline α is preferably 0.40 to 0.55 g / cm 3 More preferably, it is 0.42 to 0.55 g / cm 3 The range is more preferably 0.45 to 0.55 g / cm 3 The tapped bulk density is a value calculated by dividing the weight of the weighed crystal by the volume of a measuring cylinder filled with the weighed crystal and then manually vibrated 300 times.
[0066] <Crystal of the present invention: Crystal β> In addition, another crystal of compound A in the present invention is a crystal having an endothermic peak top temperature in the range of 120-130°C, 170-185°C and 235-245°C obtained by differential scanning calorimetry, or having diffraction peaks at diffraction angles 2θ of 11.1±0.2° and 13.4±0.2° (spectrum 1), or having diffraction peaks at diffraction angles 2θ of 10.8±0.2° and 16.9±0.2° (spectrum 2) in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, and having any one or both of the characteristics of "the above endothermic peak top temperature" and "the above powder X-ray diffraction peak spectrum (spectrum 1 or spectrum 2)" (hereinafter referred to as "crystal β").
[0067] The endothermic peak top temperature of crystal β obtained by differential scanning calorimetry is preferably in the range of 122 to 130°C, 172 to 185°C and 237 to 245°C, more preferably in the range of 123 to 130°C, 174 to 183°C and 238 to 245°C, particularly preferably in the range of 123 to 128°C, 175 to 180°C and 238 to 243°C.
[0068] Regarding the powder X-ray diffraction peak spectrum of crystal β obtained by Cu-Kα rays, in the case of spectrum 1, in addition to the above-mentioned diffraction peaks, it is preferred to have diffraction peaks at diffraction angles 2θ of 16.0±0.2° and 16.4±0.2°, and in addition to this, it is further preferred to have diffraction peaks at diffraction angles 2θ of 18.0±0.2°, 19.3±0.2°, 20.0±0.2° and 22.6±0.2°.
[0069] Regarding the powder X-ray diffraction peak spectrum of crystal β obtained by Cu-Kα rays, in the case of spectrum 2, in addition to the above-mentioned diffraction peaks, it is preferred to have diffraction peaks at diffraction angles 2θ of 13.2±0.2°, 13.6±0.2°, 14.0±0.2° and 23.6±0.2°, and in addition to this, it is further preferred to have diffraction peaks at diffraction angles 2θ of 15.9±0.2°, 20.6±0.2° and 21.6±0.2°.
[0070] The purity of compound A in crystalline β is preferably 97.0 area % or more, more preferably 97.5 area % or more, and further preferably 98.0 area % or more. The purity of compound A is calculated by the following formula using the total peak area observed when analyzing by ultra-high performance liquid chromatography, the peak area of compound A, and the peak area of various solvents by preparing a sample of a methanol solution of crystalline β at a concentration in the range of 25 to 35 mg / 50 mL.
[0071] The above-mentioned ultra-high performance liquid chromatography analysis is performed using the following analysis equipment and analysis conditions, or analysis equipment and analysis conditions equivalent thereto.
[0072] [Calculation formula] "Purity of Compound A" = ("Peak area of Compound A" ÷ "Total peak area") × {100% ÷ (100% - "Area % of various solvents")} <Equipment and Conditions> Device: Shimadzu UFLC LC-20 series / manufactured by Shimadzu Corporation Pump: LC-20AD Column oven: CTO-20A Detector: SPD-20A Chromatographic column: HALOC18 3.0×75mm / manufactured by Shimadzu GLC Corporation Incubator temperature: 50℃ Flow rate: 0.7mL / min Mobile phase: (A) 0.2 vol% acetic acid aqueous solution, (B) methanol Gradient conditions: (B) Volume % (time elapsed from the start of analysis) 50% (0 minutes) → (10 minutes) → 100% (15 minutes) Sample injection volume: 1~5μL Detection wavelength: 280nm The loose bulk density of crystalline β is preferably 0.25 to 0.40 g / cm 3 More preferably, it is 0.28 to 0.40 g / cm 3 The range is more preferably 0.30 to 0.40 g / cm 3 The loose bulk density is a value calculated by dividing the weight of the crystals filled in the measuring cylinder by the volume of the crystals measured immediately after the measuring cylinder is filled.
[0073] The tapped bulk density of the crystalline β is preferably 0.40 to 0.55 g / cm 3 More preferably, it is 0.42 to 0.55 g / cm 3 The range is more preferably 0.45 to 0.55 g / cm 3 The tapped bulk density is a value calculated by dividing the weight of the crystal filled in the measuring cylinder by the volume measured after the crystal is filled in the measuring cylinder and manually vibrated 300 times.
[0074] The present inventors have found that in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, Crystal α has diffraction peaks at diffraction angles 2θ of 7.8±0.2°, 13.8±0.2° and 16.9±0.2°. Since Crystal α can be obtained by crystallization from a solution containing cyclohexane and also contains cyclohexane after drying, it is presumed that Crystal α is a cyclohexane-solvated crystal.
[0075] In addition, for the case where two endothermic peaks sometimes appear in the differential scanning calorimetry analysis of crystal α, the inventors speculate that the peak appearing in the range of 150-165°C indicates crystal melting, and the peak appearing in the range of 237-245°C indicates crystal melting that is re-crystallized in the differential scanning calorimetry analysis. In addition, it is also confirmed that between the peak appearing in the range of 150-165°C and the peak appearing in the range of 237-245°C, there is a situation showing exothermic behavior. It is speculated that crystal α is a crystal containing one crystal phase, not a mixed crystal of multiple different crystal phases.
[0076] Regarding the situation that crystalline β has three endothermic peaks in differential scanning calorimetry, the inventors speculate that the peak appearing in the range of 120-130°C indicates that the aromatic hydrocarbon solvent with 7-10 carbon atoms solvated with the crystal is being separated, the peak appearing in the range of 170-185°C indicates crystal melting, and the peak appearing in the range of 235-245°C indicates crystal melting that is crystallized again in differential scanning calorimetry. In addition, it is also confirmed that between the peak appearing in the range of 170-185°C and the peak appearing in the range of 235-245°C, there is a situation showing exothermic behavior. It is speculated that crystalline β is a crystal containing one crystal phase, not a mixed crystal of multiple different crystal phases.
[0077] Furthermore, the present inventors found that in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, crystalline β (spectrum 1) having diffraction peaks at diffraction angles 2θ of 11.1±0.2° and 13.4±0.2° was obtained by crystallization from a solution containing toluene, contained toluene even after drying, and showed an endothermic peak in addition to the endothermic peak when the crystal was dissolved during differential scanning calorimetry analysis, thereby presuming that crystalline β (spectrum 1) was a toluene-solvated crystal.
[0078] Furthermore, the inventors found that in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, crystalline β (spectrum 2) having diffraction peaks at diffraction angles 2θ of 10.8±0.2° and 16.9±0.2° was obtained by crystallization from a solution containing ethylbenzene, and still contained ethylbenzene after drying, and in addition to the endothermic peak when the crystal was dissolved, an endothermic peak also appeared in differential scanning calorimetry analysis, thereby inferring that crystalline β (spectrum 2) is a crystal of ethylbenzene solvation.
[0079] <Method for producing crystal α> Crystal α can be produced by performing a step of crystallizing Compound A from a solution containing an alkyl acetate solvent having a total carbon number of 4 to 8 and a cyclic saturated hydrocarbon solvent having a total carbon number of 5 to 8.
[0080] Specific examples of the alkyl acetate solvent having a total carbon number of 4 to 8 include ethyl acetate (total carbon number 4), butyl acetate (total carbon number 6), amyl acetate (total carbon number 7), isoamyl acetate (total carbon number 7), 2-methylbutyl acetate (total carbon number 7), and n-hexyl acetate (total carbon number 8). Among these, butyl acetate is particularly preferred.
[0081] Specific examples of the cyclic saturated hydrocarbon solvent having 5 to 8 carbon atoms include cyclopentane and cyclohexane. Among these, cyclohexane is particularly preferred.
[0082] In addition, in order to obtain Crystal α having diffraction peaks at diffraction angles 2θ of 7.8±0.2°, 13.8±0.2° and 16.9±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, cyclohexane was used as a cyclic saturated hydrocarbon solvent having 5 to 8 carbon atoms.
[0083] As for the usage amount of these solvents, the alkyl acetate solvents having a total carbon number of 4 to 8 are preferably in the range of 0.5 to 3 times by weight, more preferably in the range of 0.5 to 2 times by weight, further preferably in the range of 0.75 to 1.5 times by weight, and particularly preferably in the range of 0.75 to 1.25 times by weight, relative to the amount of the compound A used. In addition, the cyclic saturated hydrocarbon solvents having a carbon number of 5 to 8 are preferably in the range of 1 to 5 times by weight, more preferably in the range of 1 to 3 times by weight, and particularly preferably in the range of 1 to 2 times by weight, relative to the amount of the compound A used.
[0084] In the crystallization step, it is preferred that the crystals start to precipitate when the temperature of the crystallization liquid is in the range of 50 to 100° C., more preferably in the range of 60 to 90° C., and particularly preferably in the range of 65 to 85° C. In the crystallization step, the cooling rate when cooling the crystallization liquid is preferably in the range of 5 to 20° C. per hour, more preferably in the range of 7 to 15° C. per hour, and further preferably in the range of 7 to 12° C. per hour. The final temperature of the crystallization liquid in the crystallization step is preferably in the range of 10 to 30° C.
[0085] When crystallization is precipitated, seed crystals may not be used, but seed crystals are preferably used. There is no restriction on the crystallization used as seed crystals, and crystal α is preferably used. The preparation of seed crystals of crystal α can be carried out in the crystallization process without seed crystals. The usage amount of seed crystals is preferably in the range of 0.1 to 1.0 wt % relative to compound A. The precipitated crystals can be filtered out, for example, by filtering operations such as centrifugal filtration, so that the crystals can be separated.
[0086] <Method for producing crystal β> Crystal β can be produced by performing a step of crystallizing Compound A from a solution containing an alkyl acetate solvent having a total carbon number of 4 to 8 and an aromatic hydrocarbon solvent having a total carbon number of 7 to 10.
[0087] Specific examples of the alkyl acetate solvent having a total carbon number of 4 to 8 include ethyl acetate (total carbon number 4), butyl acetate (total carbon number 6), amyl acetate (total carbon number 7), isoamyl acetate (total carbon number 7), 2-methylbutyl acetate (total carbon number 7), and n-hexyl acetate (total carbon number 8). Among these, butyl acetate is particularly preferred.
[0088] Specific examples of the aromatic hydrocarbon solvent having 7 to 10 carbon atoms include toluene, ethylbenzene, xylene, and trimethine. Among these, toluene and ethylbenzene are particularly preferred.
[0089] Furthermore, in order to obtain crystalline β having diffraction peaks at diffraction angles 2θ of 11.1±0.2° and 13.4±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα rays (spectrum 1), toluene was used as an aromatic hydrocarbon solvent having 7 to 10 carbon atoms.
[0090] Furthermore, in order to obtain crystalline β having diffraction peaks at diffraction angles 2θ of 10.8±0.2° and 16.9±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα rays (spectrum 2), ethylbenzene was used as the aromatic hydrocarbon solvent having 7 to 10 carbon atoms.
[0091] As for the usage amount of these solvents, the alkyl acetate solvent having a total carbon number of 4 to 8 is preferably in the range of 0.5 to 2 times by weight, more preferably in the range of 0.5 to 1.5 times by weight, and particularly preferably in the range of 0.75 to 1.25 times by weight, relative to the amount of the used compound A. In addition, the cyclic saturated hydrocarbon solvent having a carbon number of 5 to 8 is preferably in the range of 1 to 5 times by weight, more preferably in the range of 1 to 3 times by weight, and particularly preferably in the range of 1 to 2 times by weight, relative to the amount of the used compound A.
[0092] In the crystallization step, it is preferred that the crystals start to precipitate when the temperature of the crystallization liquid is in the range of 50 to 100° C., more preferably in the range of 60 to 90° C., and particularly preferably in the range of 65 to 85° C. In the crystallization step, the cooling rate when cooling the crystallization liquid is preferably in the range of 5 to 20° C. per hour, more preferably in the range of 7 to 15° C. per hour, and further preferably in the range of 7 to 12° C. per hour. The final temperature of the crystallization liquid in the crystallization step is preferably 10 to 30° C.
[0093] When crystallization is precipitated, seed crystals may not be used, but seed crystals are preferably used. There is no restriction on the crystallization used as seed crystals, and crystal β is preferably used. The preparation of seed crystals of crystal β can be carried out in the crystallization process without seed crystals. The usage amount of seed crystals is preferably in the range of 0.1 to 1.0 wt % relative to compound A. The precipitated crystals can be filtered out, for example, by filtering operations such as centrifugal filtration, so that the crystals can be separated.
[0094] In addition, it is preferred to further wash the crystal with a solvent. As the solvent used at this time, in the case of crystal α, a cyclic saturated hydrocarbon solvent with a carbon number of 5 to 8 is preferably used, and in the case of crystal β, an aromatic hydrocarbon solvent with a carbon number of 7 to 10 is preferably used. As the amount of the solvent used, relative to the obtained crystal, it is preferably in the range of 0.5 to 5 times by weight, more preferably in the range of 0.5 to 2.5 times by weight, further preferably in the range of 0.5 to 2 times by weight, and particularly preferably 1 time by weight.
[0095] The obtained crystals can be dried to remove the used solvent. The drying operation is preferably carried out at a temperature in the range of 20 to 100° C., more preferably in the range of 65 to 95° C., and further preferably at a temperature of 80° C. The drying can be carried out at normal pressure or under reduced pressure, but when it is carried out industrially, it is preferably carried out under a reduced pressure of about 10 kPa, more preferably under a reduced pressure of about 5 kPa, and further preferably under a reduced pressure of about 1.5 kPa. It is preferred that the solvent used be removed more efficiently when carried out under the reduced pressure.
[0096] Example The present invention will be described in more detail below with reference to Examples and Reference Examples, but the present invention is not limited to these Examples or Reference Examples.
[0097] (1) Determination of the purity and solvent content of crystalline compound A The purity of the crystalline compound A obtained in the Examples and Reference Examples and the amount of the solvent contained in the crystals were measured under the following measurement conditions.
[0098] ·Measurement conditions (A) Ultra-high performance liquid chromatography Device: Shimadzu UFLC LC-20 series / manufactured by Shimadzu Corporation Pump: LC-20AD Column oven: CTO-20A Detector: SPD-20A Chromatographic column: HALOC18 3.0×75mm / manufactured by Shimadzu GLC Corporation Incubator temperature: 50℃ Flow rate: 0.7mL / min Mobile phase: (A) 0.2 vol% acetic acid aqueous solution, (B) methanol Gradient conditions: (B) Volume % (time elapsed from the start of analysis) 50% (0 minutes) → (10 minutes) → 100% (15 minutes) Sample injection volume: 1~5μL Detection wavelength: 280nm, 254nm The purity of the obtained crystalline compound A is calculated by preparing a sample of a methanol solution having a crystal concentration in the range of 25 to 35 mg / 50 mL, and when measuring under the measurement condition (A), using the total peak area observed at a detection wavelength of 280 nm and the peak area of compound A and the peak area of various solvents, using the following formula.
[0099] [Calculation formula] "Purity of Compound A" = ("Peak area of Compound A" ÷ "Total peak area") × {100% ÷ (100% - "Area % of various solvents")} ・Measurement conditions (B) Liquid chromatography Apparatus: Shimadzu HPLC LC-20 series / manufactured by Shimadzu Corporation Pump: LC-20AT Column oven: CTO-20A Detector: SPD-20A Chromatographic column: Shimpack OLC-ODS 6mm×15cm / manufactured by Shimadzu GLC Corporation Incubator temperature: 50℃ Flow rate: 1.0mL / min Mobile phase: (A) 0.1 vol% phosphoric acid aqueous solution, (B) acetonitrile Gradient conditions: (B) Volume % (time elapsed from the start of precipitation) 50% (0 minutes) → (20 minutes) → 100% (27 minutes) Sample injection volume: 20μL Detection wavelength: 280nm, 210nm ・Measurement conditions (C) Gas chromatography Device: GC-2010 Plus / Made by Shimadzu Corporation Detection type: FID Chromatographic column: TC-160m manufactured by GL Sciences, inner diameter 0.25 mm Film thickness: 0.25μm Carrier gas: Nitrogen Column temperature: 40°C (0 minutes) → 40°C (10 minutes) → 20°C / minute → 300°C (5 minutes) Vaporization chamber temperature: 300℃ Control mode: Pressure Total flow rate: 8.5mL / min Column flow rate: 0.92mL / min Line speed: 19.9cm / sec Purge flow rate: 3.0mL / min Split ratio: 5.0 Detector temperature: 310°C Supplement flow rate: 30.0mL / min Hydrogen flow rate: 40.0mL / min Air flow rate: 400.0mL / min HS Injector Device: TurboMatrixHS40 / PerkinElmer Co., Ltd. Incubator temperature: 100°C Injection needle temperature: 105°C Transfer temperature: 105℃ Keep warm time: 20 minutes Pressurization time: 3.0 minutes Time to spare: 0.5 minutes Injection time: 0.05 minutes GC cycle time: 44.0 minutes HS carrier gas pressure: 154.0 kPa Headspace mode: Constant Vial venting: OFF The reaction yield was calculated by subtracting the amount of each solvent measured under the measurement conditions (A) to (C) from the yield of the crystals.
[0100] (2) Differential Scanning Calorimetry The crystals of Compound A obtained in Examples and Reference Examples were examined for the presence or absence of heat generation and heat absorption due to temperature using a differential scanning calorimeter (DSC) and measurement conditions as described below.
[0101] [Differential Scanning Calorimeter (DSC)] Device: DSC7020 / manufactured by Hitachi High-Technologies Corporation [Measurement conditions] Heating rate: 10℃ / min Measuring temperature range: 30~300℃ Measurement environment: Nitrogen 50mL / min Determination sample: 3~4mg crystals (3) Powder X-ray diffraction (PXRD) measurement 0.1 g of the crystals of Compound A obtained in Examples and Reference Examples were filled in the sample filling portion of a glass test plate, and powder X-ray diffraction measurement was performed using the following measuring apparatus and under the following measuring conditions.
[0102] [Measurement device] MiniFlex600-C / Made by Rigaku Co., Ltd. [Measurement conditions] X-ray source: CuKα Tube voltage: 40kV Tube current: 15mA Scan axis: 2θ / θ Mode: Continuous Measuring range: 2θ=5°~90° Step size: 0.02° Speed measurement time: 10° / minute Entrance slit: 0.25° Receiving slit: 13.00mm (4) Bulk density determination The value of the loose bulk density of the crystals obtained in Examples and Reference Examples was calculated by dividing the weight of the crystals filled in the measuring cylinder by the volume value measured immediately after the crystals were filled in the measuring cylinder.
[0103] The tapped bulk density of the crystals obtained in Examples and Reference Examples was calculated by dividing the weight of the crystals filled in a measuring cylinder by the volume measured after the crystals were filled in the measuring cylinder and manually shaken 300 times.
[0104] <Example 1> In a 2L four-necked flask equipped with a stirrer, o-cresol (69.6g), methanesulfonic acid (58.1g), and dodecyl mercaptan (4.1g) were added, and after nitrogen substitution, the temperature was raised to 50°C. A solution of o-cresol (307.7g), 4,4'-diacetylbiphenyl (79.9g), and ethylbenzene (85.3g) was prepared at 50°C, and the solution was maintained at 50°C in the flask and stirred for 5 hours to mix. Then, the mixture was stirred for 22 hours. After adding 16% sodium hydroxide aqueous solution (167.8g) and 75% phosphoric acid aqueous solution (9.7g) for rough neutralization, butyl acetate (428.0g) was added, the temperature was raised to 75°C, and the water layer was removed.
[0105] Water (211.9 g) was added to the flask to wash the oil layer with water, and then the water layer was removed. Under reduced pressure distillation was performed while heating to recover o-cresol, butyl acetate and water until the distillation residue reached 256.3 g. Then, butyl acetate (213.2 g) was added as crystallization solvent 1 to prepare a prepared solution A.
[0106] The prepared solution A (61.5 g) was taken into a 300 mL four-necked flask equipped with a stirrer, and after the liquid temperature was made to 74°C, cyclohexane (28.2 g) as the crystallization solvent 2 was added dropwise over 20 minutes. At this time, the liquid temperature dropped to 70°C. After the temperature was kept at 74°C for 35 minutes, cyclohexane (14.3 g) was added dropwise over 15 minutes. After being kept at 73°C for 1 hour, the liquid temperature was cooled to 50°C at a rate of 10°C / hour, and then cooled to 25°C. At this time, the precipitated crystals were almost not attached to the wall of the flask but were evenly dispersed in the crystallization liquid.
[0107] The precipitated crystals were filtered out with a centrifugal filter and washed with cyclohexane (26.7 g). The obtained crystals were transferred to a 200 mL eggplant flask and dried at 80° C. for 3 hours under a reduced pressure of 1.5 kPa to obtain dried crystals of Compound A.
[0108] The purity of the obtained crystalline compound A was 98.1 area %, and the yield was 68% in terms of 4,4'-diacetylbiphenyl.
[0109] The obtained crystals contained 0.8 wt % of o-cresol, 2.4 wt % of butyl acetate, and 7.4 wt % of cyclohexane.
[0110] The results of differential scanning calorimetry (DSC) of the obtained crystals showed that the melting point was 157°C from the endothermic peak temperature and that the crystal was α. The DSC data are shown in Figure 1 .
[0111] The diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 20 or more based on the peak with the strongest intensity (measured intensity) are shown in Table 1. The PXRD measurement chart is shown in Figure 2 .
[0112] [Table 1]
[0113] <Example 2> The prepared solution A (61.9 g) prepared in Example 1 was taken into a 300 mL four-necked flask equipped with a stirrer, and after the liquid temperature was made to 74°C, cyclohexane (28.4 g) was added dropwise as the crystallization solvent 2 for 20 minutes. At this time, the liquid temperature dropped to 71°C. After the temperature was kept at 73°C for 15 minutes, 80 mg of the crystal α of the compound A obtained in Example 1 was added as a seed crystal. After the addition, the temperature was kept at 73°C for 20 minutes, and cyclohexane (14.4 g) was added dropwise for a further 15 minutes. After 10 minutes, 80 mg of crystals were further added. After adding for 1 hour, the liquid temperature was cooled to 50°C at a rate of 10°C / hour, and then cooled to 25°C. At this time, the precipitated crystals were almost not attached to the wall of the flask but were evenly dispersed in the crystallization liquid.
[0114] The precipitated crystals were filtered out with a centrifugal filter and washed with cyclohexane (29.0 g). The obtained crystals were transferred to a 200 mL eggplant flask and dried at 80° C. for 3 hours under a reduced pressure of 1.5 kPa to obtain dried crystals of Compound A.
[0115] The purity of the obtained crystalline compound A was 98.5 area %, and the yield was 65% in terms of 4,4'-diacetylbiphenyl.
[0116] The obtained crystals contained 0.4 wt % of o-cresol, 2.2 wt % of butyl acetate, and 7.8 wt % of cyclohexane.
[0117] The DSC analysis results of the obtained crystals showed that the melting point was 159°C from the endothermic peak temperature and that the crystal was α. Figure 3 .
[0118] The diffraction angle 2θ (°) and relative intensity of the diffraction peaks shown in the PXRD measurement of the obtained crystal are shown in Table 2 in the same manner as in Example 1. Figure 4 From these measurement data, it is clear that the crystals obtained in Example 1 are of the same crystal system.
[0119] [Table 2]
[0120] <Example 3> The prepared solution A (63.4 g) prepared in Example 1 was taken into a 300 mL four-necked flask equipped with a stirrer, and after the liquid temperature was made to 75°C, toluene (28.2 g) was added dropwise as the crystallization solvent 2 for 20 minutes. At this time, the liquid temperature dropped to 72°C. After the temperature was maintained at 73°C for 35 minutes, toluene (14.2 g) was added dropwise for another 15 minutes. After 1 hour and 10 minutes of dropwise addition, the liquid temperature was cooled to 50°C at a rate of 10°C / hour, and then cooled to 25°C. At this time, the precipitated crystals were almost not attached to the wall of the flask but were uniformly dispersed in the crystallization liquid.
[0121] The precipitated crystals were filtered out with a centrifugal filter and washed with toluene (29.0 g). The obtained crystals were added to a 200 mL eggplant flask and dried at 80° C. for 3 hours under a reduced pressure of 1.5 kPa to obtain dried crystals of Compound A.
[0122] The purity of the obtained crystalline compound A was 98.7 area %, and the yield was 71% in terms of 4,4'-diacetylbiphenyl.
[0123] The obtained crystals contained 0.8 wt % of o-cresol, 0.6 wt % of butyl acetate, and 14.5 wt % of toluene.
[0124] The results of DSC analysis of the obtained crystals confirmed that the endothermic peak top temperatures were 125°C, 176°C, and 241°C, and that they were crystal β. The DSC data are shown in Figure 5 .
[0125] The diffraction angle 2θ (°) and relative intensity of the diffraction peaks of the obtained crystals measured by PXRD are shown in Table 3 in the same manner as in Example 1. The PXRD measurement chart is shown in Table 3. Figure 6 .
[0126] [Table 3]
[0127] <Example 4> The prepared solution A (61.8 g) prepared in Example 1 was taken into a 300 mL four-necked flask equipped with a stirrer, and after the liquid temperature was made to 74°C, toluene (28.3 g) as the crystallization solvent 2 was added dropwise for 20 minutes. At this time, the liquid temperature dropped to 69°C. After the temperature was kept at 73°C for 15 minutes, 80 mg of the crystals obtained in Example 3 were added as seed crystals. After the addition, the temperature was kept at 73°C for 20 minutes, and toluene (14.0 g) was added dropwise for a further 15 minutes. After 10 minutes, 80 mg of the crystals obtained in Example 3 were further added. After 1 hour of addition, the liquid temperature was cooled to 50°C at a rate of 10°C / hour, and then cooled to 25°C. At this time, the precipitated crystals were almost not attached to the wall of the flask but were evenly dispersed in the crystallization liquid.
[0128] The precipitated crystals were filtered out with a centrifugal filter and washed with toluene (28.2 g). The obtained crystals were added to a 200 mL eggplant flask and dried at 80° C. for 3 hours under a reduced pressure of 1.2 kPa to obtain dried crystals of Compound A.
[0129] The purity of the obtained crystalline compound A was 99.0 area %, and the yield was 74.0% in terms of 4,4'-diacetylbiphenyl.
[0130] The obtained crystals contained 0.3 wt % of o-cresol, 0.3 wt % of butyl acetate, and 14.4 wt % of toluene.
[0131] The results of DSC analysis of the obtained crystals confirmed that the endothermic peak top temperatures were 125°C, 178°C, and 242°C, and that they were crystal β. The DSC data are shown in Figure 7 .
[0132] The diffraction angle 2θ (°) and relative intensity of the diffraction peaks of the obtained crystals measured by PXRD are shown in Table 4 in the same manner as in Example 1. Figure 8 From these measurement data, it is clear that the crystals obtained in Example 3 are of the same crystal system.
[0133] [Table 4]
[0134] <Example 5> The prepared solution A (61.2 g) prepared in Example 1 was taken into a 300 mL four-necked flask equipped with a stirrer, and after the liquid temperature was made to 75 ° C, ethylbenzene (28.2 g) as the crystallization solvent 2 was added dropwise for 20 minutes. At this time, the liquid temperature dropped to 69 ° C. After the temperature was maintained at 72 ° C and stirred for 35 minutes, ethylbenzene (14.2 g) was added dropwise for another 15 minutes. After 1 hour and 10 minutes, the liquid temperature was cooled to 50 ° C at a rate of 10 ° C / hour, and then cooled to 25 ° C. At this time, the precipitated crystals were almost not attached to the wall of the flask but were evenly dispersed in the crystallization liquid.
[0135] The precipitated crystals were filtered out with a centrifugal filter and washed with ethylbenzene (28.2 g). The obtained crystals were added to a 200 mL eggplant flask and dried at 80° C. for 3 hours under a reduced pressure of 1.5 kPa to obtain dried crystals of Compound A.
[0136] The purity of the obtained crystalline compound A was 99.0 area %, and the yield was 60% in terms of 4,4'-diacetylbiphenyl.
[0137] The obtained crystals contained 0.8 wt % of o-cresol, 0.9 wt % of butyl acetate, and 15.9 wt % of ethylbenzene.
[0138] The results of DSC analysis of the obtained crystals confirmed that the endothermic peak top temperatures were 121°C, 178°C, and 241°C, and that they were crystal β. The DSC data are shown in Fig. 9 .
[0139] The diffraction angle 2θ (°) and relative intensity of the diffraction peaks of the obtained crystals measured by PXRD are shown in Table 5 in the same manner as in Example 1. Fig.10 .
[0140] [Table 5]
[0141] <Example 6> In a 5L four-necked flask equipped with a stirrer, o-cresol (282.1 g), methanesulfonic acid (225.1 g), and dodecyl mercaptan (15.8 g) were added, and after nitrogen substitution, the temperature was raised to 50°C. A solution of o-cresol (1171.6 g) and 4,4'-diacetylbiphenyl (310.1 g) was prepared at 50°C, and the solution was maintained at 50°C in the flask and stirred for 5 hours to mix. Then, the mixture was stirred for 22 hours. After adding 16% sodium hydroxide aqueous solution (624.2 g) and 75% phosphoric acid aqueous solution (14.8 g) for rough neutralization, butyl acetate (1651.2 g) was added, the temperature was raised to 75°C, and the water layer was removed.
[0142] After adding water (828.4 g) to the flask and washing the oil layer with water, the water layer was removed. While heating, vacuum distillation was performed to recover o-cresol, butyl acetate and water until the distillation residue reached 988.3 g. Then, butyl acetate (811.9 g) was added as crystallization solvent 1. After the liquid temperature was made 76°C, cyclohexane (814.9 g) was added dropwise as crystallization solvent 2 for 20 minutes. The liquid temperature at this time dropped to 68°C. After the temperature was maintained at 73°C for 10 minutes, 1.7 g of crystal α of compound A obtained in Example 2 was added as a seed crystal. After the addition, the temperature was maintained at 73°C for 15 minutes, and cyclohexane (411.3 g) was further added dropwise for 15 minutes. After maintaining at 73°C for 30 minutes, cyclohexane (641.9 g) was further added dropwise for 25 minutes. After adding for 1 hour, the liquid temperature was cooled to 59°C at a rate of 10°C / hour, and then cooled to 25°C. At this time, the precipitated crystals hardly adhered to the wall surface of the flask but were uniformly dispersed in the crystallization liquid.
[0143] The precipitated crystals were filtered out with a centrifugal filter and washed with cyclohexane (816.0 g). The obtained crystals were transferred to a 2 L eggplant flask and dried at 80° C. for 3 hours under a reduced pressure of 0.5 kPa to obtain dried crystals of Compound A.
[0144] The purity of the obtained crystalline compound A was 97.8 area %, and the yield was 67% in terms of 4,4'-diacetylbiphenyl.
[0145] The obtained crystals contained 0.5 wt % of o-cresol, 3.8 wt % of butyl acetate, and 7.8 wt % of cyclohexane.
[0146] The DSC analysis results of the obtained crystals showed that the melting point was 157°C from the endothermic peak temperature and that the crystal was α. Fig.11 .
[0147] The diffraction angle 2θ (°) and relative intensity of the diffraction peaks of the obtained crystals measured by PXRD are shown in Table 6 in the same manner as in Example 1. Fig.12 .
[0148] [Table 6]
[0149] <Example 7> In a 3L four-necked flask equipped with a stirrer, the crystals of compound A prepared in Example 6 (602.9 g) and butyl acetate (1060.0 g) were added, and the temperature was raised to 70° C. Water was added to the flask to wash the oil layer, and then the water layer was removed. The oil layer was washed with water and the water layer was removed 6 times in total, and then vacuum distillation was performed while heating to recover o-cresol, butyl acetate, and water until the distillation residue reached 1030.6 g.
[0150] After the liquid temperature was set to 80°C, cyclohexane (259.9 g) was added dropwise as the crystallization solvent 2 over 20 minutes. At this time, the liquid temperature was lowered to 75°C. 357 mg of the crystal α of compound A was added as a seed crystal, and after being kept at 75°C for 1 hour, cyclohexane (262.9 g) was added dropwise over 25 minutes. After being kept at 75°C for 20 minutes, cyclohexane (524.2 g) was added dropwise over 50 minutes. Then, the mixture was cooled to 25°C. At this time, the precipitated crystals were almost not attached to the wall of the flask but were evenly dispersed in the crystallization liquid.
[0151] The precipitated crystals were filtered out with a centrifugal filter and washed with cyclohexane (909.9 g). The obtained crystals were transferred to a 1 L eggplant flask and dried at 80° C. for 3 hours under a reduced pressure of 1.1 kPa to obtain dried crystals of Compound A.
[0152] The purity of the obtained crystalline compound A was 99.2 area %, and the yield was 51% in terms of 4,4′-diacetylbiphenyl.
[0153] The obtained crystals contained 4.7% by weight of butyl acetate and 7.6% by weight of cyclohexane.
[0154] The results of DSC analysis of the obtained crystals showed that the melting points were 161°C and 241°C from the endothermic peak temperatures and that the crystals were α. The DSC data are shown in Fig.13 .
[0155] The diffraction angle 2θ (°) and relative intensity of the diffraction peaks of the obtained crystals that appeared in the PXRD measurement, and the peaks with a relative intensity of 10 or more based on the peak with the strongest intensity (measured intensity) are shown in Table 7. The PXRD measurement chart is shown in Fig.14 .
[0156] [Table 7]
[0157] <Reference Example 1> The prepared solution A (61.6 g) prepared in Example 1 was taken into a 300 mL four-necked flask equipped with a stirrer. After the liquid temperature was set to 75°C, isooctane (27.9 g) was added dropwise as the crystallization solvent 2 for 20 minutes. At this time, the liquid temperature dropped to 72°C. In addition, the liquid in the flask was separated into two layers. After the temperature was kept at 73°C and stirred for 35 minutes, isooctane (14.1 g) was added dropwise for a further 15 minutes. After being kept at 73°C for 1 hour, the liquid temperature was cooled to 50°C at a rate of 10°C / hour, and then cooled to 25°C. Most of the precipitated solids adhered to the wall of the flask and formed blocks. After peeling off the attached blocks with a medicine spoon, the blocks were filtered out with a centrifugal filter and washed with isooctane (28.4 g). When the blocks in the flask were moved to the centrifugal filter, large blocks would clog the mouth of the flask, and other blocks would remain at the bottom of the flask, confirming that this phenomenon would become a very big problem in industrial production. In addition, due to the agglomeration, the crystals cannot be uniformly attached to the filter cloth of the centrifugal filter, and the filtering operation cannot be performed in a uniform state as a whole.
[0158] The filtered lumps were transferred to a 200 mL eggplant-shaped flask and dried at 80° C. for 3 hours under a reduced pressure of 1.5 kPa to obtain dried crystals of compound A. The dried crystals contained many lumps.
[0159] The purity of the obtained crystalline compound A was 94.5 area %, and the yield was 91% in terms of 4,4'-diacetylbiphenyl.
[0160] The obtained crystals contained 5.3% by weight of o-cresol, 2.8% by weight of butyl acetate, and 3.6% by weight of isooctane.
[0161] The DSC analysis results of the obtained crystals showed that the melting point was 101°C from the endothermic peak temperature. The DSC data are shown in Fig.15 .
[0162] The diffraction angle 2θ (°) and relative intensity of the diffraction peaks of the obtained crystals obtained by PXRD measurement are shown in Table 8 in the same manner as in Example 1. Fig.16 .
[0163] [Table 8]
[0164] <Reference Example 2> The prepared solution A (63.3 g) prepared in Example 1 was divided into a 300 mL four-necked flask equipped with a stirrer. After the liquid temperature was set to 74 ° C, methanol (29.3 g) was added dropwise as the crystallization solvent 2 for 20 minutes. At this time, the liquid temperature dropped to 69 ° C. After the temperature was kept at 69 ° C and stirred for 35 minutes, methanol (14.2 g) was added dropwise for another 15 minutes. After being kept at 69 ° C for 1 hour, the liquid temperature was cooled to 50 ° C at a rate of 10 ° C / hour, and then cooled to 25 ° C. The precipitated crystals were filtered out with a centrifugal filter and washed with methanol (28.1 g). The filtered crystals were muddy. When the crystals were moved to a 200 mL eggplant flask, it was confirmed that the funnel was stuck with muddy filtrate, and it was necessary to use a medicine spoon to push it in. In addition, when performing this operation, the crystal blocks will adhere to the medicine spoon, so it is necessary to vibrate the medicine spoon to shake off the crystals, etc., and it is confirmed that this phenomenon will become a very big problem in industrial production.
[0165] The crystals placed in the eggplant-shaped flask were dried at 80° C. for 3 hours under a reduced pressure of 1.2 kPa to obtain dried crystals of Compound A. Melting of a portion of the crystals was observed during drying.
[0166] The purity of the obtained crystalline compound A was 96.7 area %, and the yield was 80% in terms of 4,4'-diacetylbiphenyl.
[0167] The obtained crystals contained 2.7% by weight of o-cresol, 0.6% by weight of butyl acetate, and 4.3% by weight of methanol.
[0168] The results of DSC analysis of the obtained crystals showed that the endothermic peak top temperatures were 124°C and 146°C. The DSC data are shown in Fig.17 .
[0169] The diffraction angle 2θ (°) and relative intensity of the diffraction peaks of the obtained crystals measured by PXRD are shown in Table 9 in the same manner as in Example 1. Fig.18 .
[0170] [Table 9]
[0171] <Measurement of bulk density of crystals> The loose bulk density and tapped bulk density of the crystals obtained in Examples 1 to 5 and 7 were measured by the above-mentioned analytical method.
[0172] In addition, the crystals obtained in Reference Examples 1 and 2 become lumps during crystallization, filtration, or drying, and need to be crushed with a spoon for handling. Therefore, they are not uniform powders, and the measured values of bulk density vary depending on the degree of crushing of the lumps, so accurate bulk density measurement cannot be performed.
[0173] The crystallization conditions and the obtained crystals in Examples 1 to 5, Example 7 and Reference Examples 1 and 2 are summarized in Table 10. In the column "Bulk Density" in Table 10, "※" means not measured, and "-" means unable to measure.
[0174] [Table 10]
[0175] When crystallization was performed using the butyl acetate-isooctane mixed solvent of Reference Example 1, it was confirmed that the liquid separated into two layers when the solvents were mixed, most of the precipitated solids adhered to the wall of the flask and had to be peeled off with a spatula, there were many solid lumps and it was difficult to move, there were many lumps and it was not possible to evenly adhere to the filter cloth of the centrifugal filter, etc. These phenomena would become very serious problems in industrial production.
[0176] When the filter cloth of the centrifugal filter cannot be evenly attached, the passage of the filtrate or the application of the washing solvent of the filtrate becomes uneven, and the quality of the resulting crystals will be inconsistent. In addition, the vibration or noise generated by the uneven rotation during centrifugal filtration will burden the axis of the filter, thereby increasing the possibility of causing damage. These problems will become significant when large-scale manufacturing such as industrial production is carried out, and the vibration or noise may become an environmental problem around the manufacturing facility. Therefore, it is considered to be unsuitable for industrial production.
[0177] When crystallization was performed using the butyl acetate-methanol mixed solvent of Reference Example 2, the filtrate was in a muddy state. Therefore, the amount of solvent contained in the filtrate was very large, resulting in a large amount of solvent contacted by the operator handling the filtrate, thereby increasing the possibility of health problems. In addition, there was also the problem of difficulty in transportation as mentioned above. Therefore, the method was considered to be unsuitable for industrial production, as was the method of Reference Example 1.
[0178] When crystallization was carried out using the butyl acetate-cyclohexane mixed solvent of Examples 1 and 2, Examples 6 and 7, the butyl acetate-toluene mixed solvent of Examples 3 and 4, and the butyl acetate-ethylbenzene mixed solvent of Example 5, which are specific examples of the method for producing crystals of the present invention, the problems encountered in Reference Examples 1 and 2 were not confirmed.
[0179] That is, the precipitated crystals hardly adhere to the wall of the flask but are evenly dispersed in the crystallization liquid. During the filtration operation, the crystallization liquid can be smoothly transported to the filter. In addition, the filtrate is evenly attached to the filter cloth. The filtrate contains a small amount of solvent and does not adhere to the spoon, making it easy to handle.
[0180] This clearly shows that the production method of the present invention can isolate compound A as crystals, and that crystals of compound A can be efficiently obtained in industrial production.
[0181] Furthermore, when comparing the purity, it was found that the crystals obtained by the production method of the present invention were 1.4 to 4.5 area % higher than the crystals obtained by the production methods of Reference Examples 1 and 2, which also clearly showed that high-purity compound A could be obtained.
[0182] It is clear from the results of Examples 1 and 2 and Examples 3 and 4 that a crystal with a higher purity can be produced by adding a seed crystal.
Claims
1. A crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl.
2. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to claim 1, characterized in that The endothermic peak top temperature obtained by differential scanning calorimetry analysis was in the range of 150 to 165°C.
3. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to claim 1, characterized in that In the powder X-ray diffraction peak spectrum obtained by Cu—Kα rays, there are diffraction peaks at diffraction angles 2θ of 7.8±0.2°, 13.8±0.2°, and 16.9±0.2°.
4. A method for producing a crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to claim 1 or 2, characterized in that: The invention comprises the step of crystallizing 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl from a solution containing an alkyl acetate solvent having a total carbon number of 4 to 8 and a cyclic saturated hydrocarbon solvent having a total carbon number of 5 to 8.
5. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to claim 1, characterized in that The endothermic peak top temperatures obtained by differential scanning calorimetry analysis were in the range of 120 to 130°C, 170 to 185°C, and 235 to 245°C.
6. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to claim 1, characterized in that In the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, there are diffraction peaks at diffraction angles 2θ of 11.1±0.2° and 13.4±0.2°.
7. The crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to claim 1, characterized in that In the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays, there are diffraction peaks at diffraction angles 2θ of 10.8±0.2° and 16.9±0.2°.
8. A method for producing a crystal of 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl according to claim 1 or 5, characterized in that: The invention comprises the step of crystallizing 4,4'-bis(1,1-bis(4-hydroxy-3-methylphenyl)ethyl)biphenyl from a solution containing an alkyl acetate solvent having a total carbon number of 4 to 8 and an aromatic hydrocarbon solvent having a total carbon number of 7 to 10.
Citation Information
Patent Citations
Polyphenol, epoxy resin, epoxy resin composition and its cured material
JP1996027052A
Lift-off resist composition
JP2001235872A
